If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-3x+4=-4(2x+1)
We move all terms to the left:
-5x-3x+4-(-4(2x+1))=0
We add all the numbers together, and all the variables
-8x-(-4(2x+1))+4=0
We calculate terms in parentheses: -(-4(2x+1)), so:We get rid of parentheses
-4(2x+1)
We multiply parentheses
-8x-4
Back to the equation:
-(-8x-4)
-8x+8x+4+4=0
We add all the numbers together, and all the variables
8!=0
There is no solution for this equation
| 5(x+3)+1/5(5x+10)=11 | | 7(2x–5)−5(3x+1)=6(x–4)–7 | | 70=(d+7) | | 0.5x^2-x+8=0 | | y^2–5y+6=0 | | 5(4x+8)=x | | -5x+10=10-2x-3x | | 40+15+x=180 | | 15/25=18/x | | -14+2x+3=4x-13+7x | | 5x-6=6-5x | | (3x=6)+(4x-6) | | p/8-4=-33 | | 9+12w=12w-6 | | 6x+1=2+6x | | 2x-3=21+12+4 | | 16x+20=1.50x | | 7y-12=13 | | 1+z/14=0 | | 4=8x−12 | | 8x–12=–20 | | 50x+3350x-80=68(50x+62) | | 4-104/v=4 | | -5x+4=3x−12 | | 5=15p+2 | | 2a+7-5a+8=3(5+6a)-12a | | 4−3a=8a+7 | | 6x(3x-1)=2x+3 | | 9x-13=2x+35 | | 27-v=286 | | -4(2a-8)+4=20 | | 3y-15=2y+8 |